Dilemas federativos e construção de capacidades em nível local : uma análise dos fatores associados ao FUNDEB na educação infantil - Ferreira, Victor Barcelos (2020)
This research aimed to explore the educational inequality issue and its relation with dilemmas that occur as a consequence of federative pact and its distribution of educational responsibilities. Inside this area, the main object will be analyzed it is the Fund for the Development of Basic Education and Appreciation of the Teaching Profession (Fundo de Manutenção e Desenvolvimento da Educação Básica e de Valorização dos Profissionais da Educação – Fundeb) and its factors associated to early childhood education. Two key points sight this research, which is: the effectiveness of Fundeb to create incentives to the municipalities to extend the free early childhood education access in Brazil, and, related to this, the capacity to promote a more equitable system. First, it was analyzed the current situation of early childhood education in Brazil and Brazilian regions. Secondly, the research investigates the effects which educational fund policy may have influenced in infrastructural power on early childhood education attend. Here, it is considering the capacity of the state to penetrate its territories and provide public goods as the definition of infrastructural power. Therefore, the research explored the expansion of municipal early childhood education schools in the state of Minas Gerais. The evidences point to the institutional framework, which Fundeb is included in, induces to ambiguous incentives, since it produces different results between kindergarten and preschool, when both are compared to each other. Besides this, the findings of this research suggest that the redistribution mechanisms can reinforce inequalities, either in horizontal and vertical levels, then weakening the low technical and financial capacity municipalities and, on the other hand, strengthening the other ones. In the same way, the fact of every fund operates only in the state level, embracing municipalities and its state government, can prejudice low fiscal capacity, and even with the Union complementation, the arrangement did not show to be effective to promote equality results in educational access around the country. This research aims to show gains and losses produced by early childhood education insertion in educational policy, to then, make room for suggestions to the redesign in order to improve the incentives are set.